PERAN BELIS SEBAGAI ALAT KONTROL DALAM PERKAWINAN ADAT: STUDI KASUS DI KABUPATEN SIKKA - Cecilia Djawa (FEB Universitas Sam Ratulangi Manado, 2023)
The high number of divorce cases reflects the failure to achieve the goal of marriage. Therefore, a control tool is needed so that the purpose of marriage can be achieved. The purpose of this study is to see how far the role of belis culture plays as a control tool in marriage to achieve the goal of a happy and lasting marriage. This research is a qualitative research using a case study approach in Sikka, Indonesia. Data collection method used is in-depth interviews. The results of the study show that belis customary marriage acts as a means of controlling the behavior of the bride and groom in achieving the goal of a happy and lasting marriage until death do them part. The goal of lasting marriage can be achieved by imposing belis so as to minimize the risk of divorce triggered by problems such as domestic violence and infidelity. Future research can use other cultures such as the culture of death or the culture of eating from various regions in Indonesia so that there is more literature on management control systems in terms of culture and can make observations so as to enrich research data. Keywords : Belis; Control; Culture; Management Control System; Marriage